2007
DOI: 10.1084/jem.20062512
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine generation catalyzed by CD39 and CD73 expressed on regulatory T cells mediates immune suppression

Abstract: The study of T regulatory cells (T reg cells) has been limited by the lack of specific surface markers and an inability to define mechanisms of suppression. We show that the expression of CD39/ENTPD1 in concert with CD73/ecto-5′-nucleotidase distinguishes CD4+/CD25+/Foxp3+ T reg cells from other T cells. These ectoenzymes generate pericellular adenosine from extracellular nucleotides. The coordinated expression of CD39/CD73 on T reg cells and the adenosine A2A receptor on activated T effector cells generates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
1,916
8
48

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 2,054 publications
(2,035 citation statements)
references
References 39 publications
63
1,916
8
48
Order By: Relevance
“…We found that in steady state, POM‐1 treatment significantly reduced accumulation of CD45 + Lineage (Lin, CD3/B220/CD11c/CD11b/NK1.1) − CD90.2 + RORγt + ILC3s, but not activated IL‐22‐producing ILC3s, in the colon (Figure 2d, e and Supplementary figure 4). In addition, POM‐1 also decreased colonic IL‐22 + CD3 + T cells as well as Foxp3 + Tregs (Figure 2e–g), the latter was in agreement with previous findings showing that NTPDases (especially CD39) are critical for Treg development and function 11. Administration of DSS did not change the numbers of RORγt + ILC3s in the colon but increased colonic IL‐22 + ILC3s by ~4‐fold while colonic IL‐22 + CD3 + T cells were not changed by DSS (Figure 2d, e, h, i).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…We found that in steady state, POM‐1 treatment significantly reduced accumulation of CD45 + Lineage (Lin, CD3/B220/CD11c/CD11b/NK1.1) − CD90.2 + RORγt + ILC3s, but not activated IL‐22‐producing ILC3s, in the colon (Figure 2d, e and Supplementary figure 4). In addition, POM‐1 also decreased colonic IL‐22 + CD3 + T cells as well as Foxp3 + Tregs (Figure 2e–g), the latter was in agreement with previous findings showing that NTPDases (especially CD39) are critical for Treg development and function 11. Administration of DSS did not change the numbers of RORγt + ILC3s in the colon but increased colonic IL‐22 + ILC3s by ~4‐fold while colonic IL‐22 + CD3 + T cells were not changed by DSS (Figure 2d, e, h, i).…”
Section: Resultssupporting
confidence: 93%
“…ILC3s) in addition to reported mechanisms via regulation of the adaptive immune system (e.g. Treg and Th17/Th1 cells) 11, 12, 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism leading to suppression of T-cell mediated immune responses is excessive production of adenosine by the cell surface enzyme CD73 (ecto-5′-nucleotidase) [128,129]. CD73 is usually expressed on endothelial and epithelial cells [130], subsets of leukocytes [131] and Foxp3 + Tregs [128,129], but also on several cancer types [132,133].…”
Section: Other Immunosuppressive Moleculesmentioning
confidence: 99%
“…CD73 is usually expressed on endothelial and epithelial cells [130], subsets of leukocytes [131] and Foxp3 + Tregs [128,129], but also on several cancer types [132,133]. CD73 acts in concert with CD39 (ecto-apyrase) to produce adenosine in a coordinated two-step enzymatic conversion.…”
Section: Other Immunosuppressive Moleculesmentioning
confidence: 99%